Case Report: A Rare Case of Severe Coronary Venous Spasm During Radiofrequency Ablation of Premature Ventricular Contraction - Sha, Rina; Rong, Bing; Maduray, Kellina; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2022)
Coronary venous spasm has never been reported during premature ventricular extrasystole ablation. We report a 20-year-old female patient who experienced severe spasm of the great cardiac vein during radiofrequency ablation for premature ventricular contractions, which was relieved eventually by administration of intracoronary nitroglycerine. The operation was successfully completed, leading to long-term resolution of her palpitation symptoms.